Microbiome analysis of andean soils and high-throughput molecular aproaches for translational epidemiology of early blight - Alvarez Romero, Pablo Israel (Universidade Federal de Viçosa, 2019)
Early blight (EB) is one of the most devastating foliar diseases of solanaceous crops. As chemical control is the main strategy used to control EB, the active microbiota of the soil has the potential to help to managing plant diseases. It was demonstrated that the microbiota associated with Andean soils has an important role in potato diseases suppressiveness. Based in this hypothesis we used high-throughput sequencing (HTS) and metabarcoding to investigate the composition, structure, and diversity of microbiota associated with the rhizosphere of native (landraces) and improved potatoes (commercial) from the Ecuadorian Andes as a quest for potential biological control agents of early blight. The main fungi phyla found were Ascomycota (51.96%), Mortierellomycota (28.39%) and the Basidiomycota (5.56%), while bacterial community was dominated by the Proteobacteria (39.17%), Acidobacteria (17.89%), and Bacteroidetes (14.10%) phyla. Edaphic factors affected the composition, diversity, and structure of the microbiota across the different places sampled. Higher microbial diversity was found in the rhizosphere from landrace cultivars and it constitutes a new source of candidate microorganisms for the use in biological control. Moreover, we used an ecological approach involving reciprocal soil transplant to test the effect of putative suppressive Andean soils to potato and tomato EB epidemics. The direct transfer of soil had an effect only on the epidemics on potato EB. The rhizosphere microbiome from the plants was structured by soil and crop type. Highest levels of fungal diversity were found in potato rhizosphere associated with Ecuadorian soils. Also in the same study, we used HTS and metabarcoding to assess the temporal variation of the fungal and bacterial leaf-microbiota associated with potatoes and tomatoes plants growth in Brazilian and Ecuadorian soils and infected by different species of Alternaria. The leaf profile of microbiota composition was affected by the soil transfer. Thirteen families of fungi belonging to the Ascomycota phylum and 15 families belonging to the Basidiomycota were found in potatoes associated with Brazilian soils, in contrast, eight families of fungi belonging to Ascomycota phylum and 17 families belonging to the Basidiomycota phylum were found in potatoes associated with Ecuadorian soils. Also, 15 families of Fungi belonging to Ascomycota and 10 families belonging to Basidiomycota were found in tomatoes grown in Brazilian soil while, respectively, 14 and 16 families were recorded in plants grown in Ecuadorian soil. Finally, to differentiate closely related species of Alternaria associated with EB in potato and tomato crops, a single round polymerase chain reaction coupled with high-resolution melting curve (PCR-HRM) using primers for the cadmodulin gene were develop and validated. The HRM-assay was a useful diagnostic tool. All techniques explored in this thesis may enhance management strategies for early blight epidemics. Keywords: Metabarcoding. Sequencing. Soil Suppressiveness. Alternaria. PCR. Population biology.

A pinta preta (PP) é uma das doenças mais devastadoras das solanáceas. A pesar de a aplicação de fungicidas ser a principal estratégia para o controle da PP, a microbiota ativa do solo tem o potencial de contribuir para o manejo de doenças de plantas. Foi demonstrado que a microbiota associada aos solos andinos tem papel importante na supressividade das doenças da batata. Com base nessa hipótese, utilizamos o sequenciamento de alto rendimento (SAR) e metabarcoding para investigar a composição, estrutura e diversidade da microbiota associada à rizosfera de batatas nativas e melhoradas dos Andes equatorianos para uma busca de potenciais agentes de controle biológico da PP. Os fungos encontrados foram predominantemente representado por indivíduos dos filos Ascomycota (51,96%), Mortierellomycota (28,39%) e Basidiomycota (5,56%), enquanto a comunidade bacteriana foi dominada pelos filos Proteobacteria (39,17%), Acidobacteria (17,89%) e Bacteroidetes (14,10%). Fatores edáficos afetaram a composição, diversidade e estrutura da microbiota nos diferentes locais amostrados. Maior diversidade microbiana foi encontrada na rizosfera dos genótipos nativos que constituem uma nova fonte de microrganismos candidatos para uso no controle biológico. Além disso, utilizou-se uma abordagem ecológica envolvendo o transplante de solo recíproco para testar o efeito de potenciais solos supressivos andinos nas epidemias de PP em batata e tomate. A transferência direta de solo teve efeito apenas sobre as epidemias de PP em batata. O microbioma da rizosfera das plantas foi estruturado por solo e tipo de cultura. Os maiores níveis de diversidade fúngica foram encontrados na rizosfera de batatas associada aos solos equatorianos. Também no mesmo estudo, utilizou-se SAR e metabarcoding para acessar a variação temporal da microbiota fúngica e bacteriana associadas às plantas de batata e tomate infectadas por diferentes espécies de Alternaria e crescidas em solos brasileiros e equatorianos. O perfil foliar da composição da microbiota foi afetado pela transferência de solo. Treze famílias de fungos pertencentes ao filo Ascomycota e 15 famílias pertencentes ao filo Basidiomycota foram observadas em batatas associadas a solos brasileiros. Em contrapartida, oito famílias de fungos pertencentes ao filo Ascomycota e 17 famílias pertencentes ao filo Basidiomycota foram observadas em batatas associadas a solos equatorianos. Além disso, 15 famílias de fungos pertencentes a Ascomycota e 10 famílias pertencentes a Basidiomycota foram observadas em tomates cultivados em solo brasileiro, enquanto em plantas cultivadas em solo equatoriano foram registradas 14 e 16 famílias de fungos pertencentes a Ascomycota e Basidiomycota, respectivamente. Finalmente, para diferenciar as espécies de Alternaria associadas à PP em plantações de batata e tomate, uma reação de polimerase em cadeia única acoplada à curva de dissociação de alta resolução (PCR-HRM) foi desenvolvida e validada utilizando primers desenhados com base nas diferenças de nucleotídeos da região calmodulina. O ensaio HRM foi uma ferramenta de diagnóstico útil para melhorar as estratégias de manejo para epidemias de PP. Palavras-chave: Metabarcoding. Sequenciamento. Supressividade de solo. Alternaria. PCR. Biologia de populações.
Análise de microbioma de solos andinos e abordagens moleculares de alto rendimento para epidemiologia translacional de pinta preta
Keywords: Alternaria; Analise de Sequencia, DNA; Micro-organismos do solo; Fitopatologia